Highly efficient and practical aerobic oxidation of alcohols by inorganic-ligand supported copper catalysis. Issue 15 (3rd July 2019) - Wei, Zheyu; Ru, Shi; Zhao, Qixin; Yu, Han; Zhang, Gang; Wei, Yongge
Abstract : An inorganic-ligand supported copper catalyst which can effectively catalyze the aerobic oxidation of alcohols to afford aldehydes or ketones with excellent selectivity and yields. Abstract : The oxidation of alcohols to aldehydes or ketones is a highly relevant conversion for the pharmaceutical and fine-chemical industries, and for biomass conversion, and is commonly performed using stoichiometric amounts of highly hazardous oxidants. The aerobic oxidation of alcohols with transition metal complex catalysts previously required complicated organic ligands and/or nitroxyl radicals as co-catalysts. Herein, we report an efficient and eco-friendly method to promote the aerobic oxidation of alcohols using an inorganic-ligand supported copper catalyst1, (NH4 )4 [CuMo6 O18 (OH)6 ], with O2 (1 atm) as the sole oxidant. Catalyst1 is synthesized directly from cheap and commonly available (NH4 )6 Mo7 O24 ·4H2 O and CuSO4, which consists of a pure inorganic framework built from a central Cu II core supported by six Mo VI O6 inorganic scaffolds. The copper catalyst1 exhibits excellent selectivity and activity towards a wide range of substrates in the catalytic oxidation of alcohols, and can avoid the use of toxic oxidants, nitroxyl radicals, and potentially air/moisture sensitive and complicated organic ligands that are not commercially available. Owing to its robust inorganic framework, catalyst1 shows good stability and reusability, and the catalytic oxidation of alcohols with catalyst1 could be readily scaled up to gram scale with little loss of catalytic activity, demonstrating great potential of the inorganic-ligand supported Cu catalysts in catalytic chemical transformations.